A class of Pt(iv) triple-prodrugs targeting nucleic acids, thymidylate synthases and histone deacetylases. Issue 5 (5th February 2020) - Ding, Xiao-Jing; Zhang, Ran; Liu, Rui-Ping; Song, Xue-Qing; Qiao, Xin; Xie, Cheng-Zhi; Zhao, Xiu-He; Xu, Jing-Yuan
Abstract : A Pt(iv )-triple-prodrug, comprising VPA, 5-FU, regulated TS, HDAC, and γH2AX, showing higher efficiency and lower toxicity than cisplatin. Abstract : A series of Pt(iv ) compounds comprising a special short-chain fatty acid (a histone deacetylase inhibitor) and 5-FU (a thymidylate synthase inhibitor) were prepared and bio-evaluated for their antiproliferative activity using the MTT assay. The assembled compounds 11–15, as triple-prodrugs, exhibited a potent anti-cancer activity. In particular, compounds 14 and 15 both with valproic acid (VPA) showed higher potent cytotoxicity against the tested cancer cells, whereas lower cytotoxicity toward normal human umbilical vein endothelial cells than the free drugs involved. Compound 14, as a representative for further study, rapidly enhanced the cellular accumulation in a time-dependent manner, significantly induced the DNA-damage, cell cycle blocking at the S phase, and cell apoptosis as well as suppressed migration in HeLa. Most strikingly, compound 14 simultaneously regulated the TS, HDAC and γH2AX factors, suggesting a synergistic action of 5-FU, VPA and CDDP to increase the drug effects.